The Influence of Service Quality and Content Marketing on the Purchase Decision in Using the Menggala Express Bus Service on the Surabaya – Malang Route - Zidane Fernanda Kusuma; Sugeng Purwanto; Virginia Mandasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to determine the effect of Service Quality and Content Marketing on purchasing decisions in using PO Menggala bus services among users on the Surabaya–Malang route. A quantitative methodology was employed in this study, where data were gathered through questionnaire distribution and subsequently analyzed using the PLS-SEM approach via the SmartPLS application. The research involved 105 participants selected based on purposive sampling criteria. The results indicate that both Service Quality and Content Marketing have a positive and significant influence on purchasing decisions. These findings confirm that excellent service and informative, engaging digital content play a crucial role in shaping consumer preferences toward transportation services. Promotion strategies emphasizing passengers' real-life experiences through social media have proven effective in influencing purchasing decisions for PO Menggala bus services.